PENGARUH KARAKTERISTIK INDIVIDU DAN FAKTOR LINGKUNGAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pembelian Produk Asuransi Jiwa Unit Link Di Jakarta) - Devi Krisnawati (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This research use descriptive research with quantitative approach. There are three variables that are used in this research: Individual Differences, Environmental Factors and Buying Decision. The collection of data obtained through online questionnaires, which were distributed randomly in Jakarta. The sample in this research was 100 respondents. The sampling technique of this research is random sampling. The data analysis uses descriptive analysis and multiple linear regressions. The results in this research showed that Individual Differences and Environmental Factors simultaneously affecting Buying Decision significantly. The other results showed that Individual Difference and Environmental Factors partially affecting Buying Decision significantly. Based on the result of this research, it’s better for Insurance Company to considerate people personal individual differences and also environmental factors to strengthen the sales of unit link product.